Transition metal dichalcogenide (tmd) nanosheets and fullerenes for beyond lithium-ion storage: a study of composite structure engineering and voltage-cutoff optimization - Dey, Sonjoy (Kansas State University, 2023)
The insatiable appetite for energy storage technologies has pushed the boundaries of innovation – enabling humans to transition from fossil fuel-based inefficient, environmentally unsustainable equipment to e-mobility devices/vehicles – three decades ago, which was thought to be unattainable. Most of such achievements are due to the proliferation of Li⁺ ion-based rechargeable energy storage devices. But today, the depletion of resources (limited supply of Li) leading to cost increase has made it clear that developing alternative technologies and taking proper measures is imperative. With similarities in chemistry and working principles - providing ease in technological development and abundance due to precursors in natural resources like water, sodium, and potassium ion-based storage systems are considered the best alternatives. However, while advancements in LIB technology have reached their acme, developments in Sodium-ion batteries (NIBs) and Potassium-ion batteries (KIBs), specifically different cell components like electrodes and electrolytes, are nowhere near their peak. Therefore, this thesis aims to investigate novel, negative electrode materials for state-of-the-art NIBs and KIBs. With Novoselov and Geim’s discovery of individual Graphene nanosheets, two-dimensional (2D) materials have received uplifted interest for various applications. In this scenario, Transition Metal Dichalcogenides (TMDs) with similar lamellar structure and versatile chemistry present further opportunities with attractive properties – comparatively higher uptake and faster diffusion of Li⁺, Na⁺, and K⁺ ions being some of them. Although 2019 Nobel Prize winner in Chemistry, M. Stanley Whittingham, in the early 70s, started investigating the electrochemical properties of TMDs; the research was inevitably short-lived due to the poor stability of such classes of material. This report, therefore, examines in detail the fascinating properties of distinctive nanostructures of TMDs – where solutions to research challenges are yet to be proposed. One inherent issue that all TMD-based electrodes face while applied as Li⁺-based storage systems is the irreversibility of the conversion reaction. On top of that, when storage of larger ions such as Na⁺/K⁺ is considered, further complexities arise as volume changes and subsequent pulverization of materials occur. The first two studies involve composite structure formation using different nanostructures of sulfide-based TMDs, specifically WS₂ nanosheets (WS₂NS) and WS₂ nanotubes (WS₂NTs), to rectify the abovementioned intricacies. The composite structure was fabricated utilizing a chemically robust molecular polymer-derived ceramic matrix of silicon-oxycarbide (SiOC). As various studies have assessed the efficacy of high volume-to-strength ratio fiber-containing nanofillers, herein, we first investigated the fiber production feasibility using WS₂NS and WS₂NTs embedded within ceramic SiOC fibers utilizing electrospinning followed by pyrolysis at elevated temperatures. The pyrolyzed fibers containing WS₂NS and WS₂NTs, when tested beyond Li⁺-based storage systems, demonstrated synergistic effects – rendering 2-3 times the capacity of the neat material. Furthermore, the typical capacity fading behavior of the neat TMDs was also absent in the composite electrodes – providing the basis for the initial hypothesis that SiOC fibers protect the nanofillers from degradation. The third study investigated a different nanostructure of sulfide-based TMDs, namely WS₂ inorganic fullerenes (WS₂IFs), beyond Li⁺ ion storage applications. Such closed cage fullerene-like structures have been previously studied in light-matter interaction – that extensively encompasses application fields of frequency conversion, optical imaging, and information processing. Additionally, their usage as lubricants or protective films for high load-bearing applications has been explored in depth. Being motivated by the numerous attractive properties and layered structure of WS₂IFs, they were applied to Na⁺ and K⁺ ion storage applications. Like the typical TMD nanosheets, such WS₂IFs also suffer from irreversible conversion reactions for which inefficiency in cycling behavior was observed – leading to capacity fading when larger ions than Li⁺ are stored. Therefore, we utilized upper and lower voltage cut-off techniques to suspend conversion reactions at various stages. The kinetics of Na⁺ and K⁺ ion storage within WS₂IFs were further explored by employing different electrochemical analysis techniques – rendering the faradaic and non-faradaic processes taking place. With higher capacity achievement in the case of Na⁺ ion storage and higher coulombic efficiency realization in Li⁺/Na⁺/K⁺ ion storage, this study lays the ground for future studies concerning efficient storage within cage-bound like fullerene structures. Fine-tuning the physical properties of TMD nanosheets by continuous modulation of elemental composition has resulted in further band structure optimization – therefore, substituting metal or chalcogen atoms has rendered a new class of material such as TMD alloys, which expands the versatility of TMD nanosheets. In the fourth work, a cation-substituted TMD alloy, namely MoWSe₂¬ in its nanosheet form, was utilized in its nanosheet form to explore the Na⁺ and K⁺ ion storage properties. This investigation also used the upper voltage cut-off experiment to curb the increased conversion reaction from two transition metals. Three-dimensional (3D) surface plots of differential capacity analysis up to prolonged cycles revealed the convenience of voltage suspension as a viable method for structural preservation. Moreover, the cells with higher potential cut-off values conveyed improved cycling stability, higher and stable coulombic efficiency for Na⁺ and K⁺ ion half-cells, and increased capacity retention for Na⁺ ion half-cells, respectively, with half-cells cycled at higher voltage ranges. Selenide-based TMDs (MoSe₂) were fabricated with SiOC matrix employing electrospinning technique further to test the viability of composite formation with TMD nanosheets. Finally, mechanical testing of the composite fibers was implemented to investigate the practicability of such fibermats in next-generation bendable, stretchable, free-standing devices.
Keywords: Transition metal dichalcogenide (TMD); Sodium-ion batteries (NIB); Potassium-ion batteries (KIB); Composite electrode; Lithium-ion batteries (LIB); Beyond lithium storage